Prevalence and Outcomes of Cardiovascular Diseases in Patients with COVID-19: A Research Letter - Patel, MD, Ghanshyam; Vasavada, MBBS, Advait; Reddy, DO, Shilpa; Adak, MBBS, Shrestha; Jain, MBBS, Shikha; Regassa, MD, Henok; Korsapati, MD, PhD, Hariprasad Reddy; Korsapati, MD, Aishwarya Reddy; Chand, MD, Mool; Mukesh, MD, Sindhu; et al. (International Journal of Innovative Research in Medical Science, 2022)
Introduction A higher prevalence of cardiovascular diseases among COVID-19 with positive troponin levels was initially observed in China beginning of the pandemic era. We are trying to add to the material available with demographics and prevalence of cardiovascular disease among COVID-19 positives. SARS-CoV-2 is mainly a respiratory disease, but it can involve a heart with direct virulence through ACE-2, exaggerated inflammatory reaction, micro thrombosis, and endothelial injury [1]. We conducted a retrospective analysis to determine cardiovascular disease prevalence among these populations stratified by troponin levels. Cardiovascular diseases led to an increase in the rate of morbidity and mortality among COVID-19 patients. The viral infection in severe cases causes cytokine storm and hypercoagulability that manifests in various acute cardiovascular events like myocardial infarction, heart failure, and myocarditis or thrombotic events like pulmonary embolism and DIC [2]. There is also a high incidence of arrhythmia observed in cases with COVID-19 likely because of viral infection, QT-prolonging medications including antibiotics and anti-viral. The overall burden of cardiovascular diseases, demographics, and co-morbidities in COVID-19 patients has been described in the literature but no causal relationship between them has been explored [3]. Also, there is little evidence regarding the characteristics of patients with myocardial injury [4]. Hence, further evidence on the subject can aid better evidence-based decisions on the prevention of acute cardiac events. A retrospective observational study was conducted of patients with a clinical diagnosis of COVID-19 from January 2020 to December 2021 in a large community health service. Patients were included if they had a laboratory or nasal swab confirmed SARS-CoV-2 infection. Myocardial injury was defined as high-sensitive troponin T levels 99th percentile above the upper limit of normal for respective biological sex (22ng/ml for female; 14ng/ml for male). The primary outcome was to find out prevalence of cardiovascular disease among COVID-19 patients stratified by troponin level. Descriptive analyses were performed by troponin level divided into positive and negative. We evaluated demographic, baseline characteristics, and medical history of cardiovascular diseases. The categorical variables are reported as total count and percentage with their p-value based on the chi-square test. A total of 13560 (45.3 % Male, 21.5 % aged >65 years) patients with COVID-19 were included, out of which 411 (3%) had a myocardial injury. Patients with myocardial injury were older (75.9% >65 years) and had higher cardiovascular-related comorbidities when compared with those without. The male and females were equally distributed (49.4% vs 45.2%, 50.6% vs 54.8%; Male and Female respectively). The population in this study was predominantly white (85.2% vs 86.4%) and non-Hispanics (92.2% vs 85.2%). The overall cardiovascular diseases and cardiovascular risk factors were markedly higher in the myocardial injury group. The overall prevalence of Hypertension, Diabetes, and Dyslipidemia were 34.8%, 38.8%, and 36.8% respectively among patients with COVID-19. Troponin positive group had higher dyslipidemia, myocardial infarction (MI), unstable angina, coronary artery disease, cardiomyopathy, heart failure, arrhythmias, stroke, and peripheral arterial disease (PAD). Hospitalization was higher in troponin-positive patients compared to those in troponin negative group (75.9% vs 10%). Length of stay and use of mechanical ventilation was higher in troponin-positive patients. The mortality among troponin-positive strata was 19.7 % versus 1.6 % in troponin-negative strata. In our study, we found the prevalence of cardiovascular diseases was much higher among Covid-19 patients with positive troponin levels. The main finding, confirming this study, is that the prevalence of cardiovascular diseases is significantly increased among patients with troponin positive and that this increase can be attributable to traditional risk factors. One previous study found 56.1 % of prevalence of myocardial injury among hospitalized COVID-19 patients [5]. Further research may be needed to understand the pathophysiology of Covid-19 affecting cardiovascular diseases.